Szanse zawodowe młodych w okresie kryzysu gospodarczego = Young Europeans on the labour market and their professional chances during the economic crisis - Foltyniewicz, Aneta (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The analyses presented in the article are quantitative. Their major aim is to show the changes in the life choices of young Poles and young Europeans during the economic crisis. Using the ESS data, the author compares the decisions made by young people in Poland and other 20 European countries at three time points - in 2006, i.e., in the "pre-crisis time", in 2008 - the beginning of the crisis and 2010 - its deeper phase. She analyses how, over the four-year-period, the proportions of the respondents change - respondents who decide to choose one of the path in life: education, work, labour migration.
Keywords: labour market; chances to find first job; young Europeans; education; migrations; quantitative analyses; macroeconomic indicators; comparative analyses; European Social Survey (ESS); rynek pracy; szanse na znalezienie pierwszej pracy; młodzi Europejczycy; edukacja; migracje; analiza ilościowa; analiza porównawcza; wskaźnik makroekonomiczny; Europejski Sondaż Społeczny